Tinjauan Undang-Undang Nomor 19 Tahun 2002 Tentang Hak Cipta Dan Hukum Islam Mengenai Kedudukan Hak Cipta - Ahmad, Rafliyanto; Thalib, Muthia Cherawaty; Mustika, Waode (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Copyright law protection has basically been regulated in Law Number 19 of 2002 Concerning Copyrights. The Act has regulated in detail regarding copyright. However, in reality there are very many violations of copyright, especially violations committed via the internet. The research questions in this thesis are how to review Law Number 19 of 2002 concerning Copyright and Islamic Law concerning the status of copyright, what are the forms of copyright infringement carried out via the internet and how is the legal protection for copyright holders in Law Number 19 of the Year 2002 Concerning Copyright and Islamic Law. This study uses library research techniques (library research) and is in the form of descriptive analysis which is a systematic description of existing facts accurately and factually. From the results of the study it was found that copyright is among patents, trademarks and other rights in under intellectual property rights (IPR) protected by the state, in Islam also copyright is equated with haqq al-milk (ownership rights) which is a division of haqq al-māl because Islam recognizes copyright as al-māl (property). Law Number 19 of 2002 concerning Copyright stipulates penalties for copyright violators in the form of a minimum fine of IDR 1,000,000 and a maximum of IDR 5,000,000,000 and also imprisonment for a minimum of one month in prison and a maximum of seven years in prison. In Islam it has also been regulated that copyright infringers are subject to ta'zīr laws in the form of jild (flogging), ḥabs (imprisonment) or other penalties which can be heavier or lighter. Thus, it can be concluded that the existence of copyright is recognized and protected by Law Number 19 of 2002 concerning Copyright and Islamic Law.